Studi Efisiensi Hasil Perubahan Sistem Jaringan Irigasi Berbasis SIG (Sistem Informasi Geografis) pada Daerah Irigasi Kajar 2D, Kajar 2E, Kajar 2F, dan Kajar 2G Kecamatan Lowokwaru, Kota Malang - Rafif, Hanif; Prayogo, Tri Budi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Referring to the conditions in Lowokwaru sub-district, there was a reduction in the area of rice fields due to an increase in the conversion of paddy fields to residential areas. This study aims to determine changes in the irrigation network system that affect the water distribution system in the irrigation area. This study was conducted using data from 2012 and 2017 which includes a comparative analysis of rice fields using the arc GIS application. analysis of existing irrigation network conditions for comparison of clean water needs of paddy fields. and analysis of the difference in the efficiency of the use of water needs to show whether or not it is still feasible to irrigate the reduced fields due to land use changes in each of the irrigation areas. The results of the study include a comparative analysis of rice fields_Area is losing 9%, losing 7%, losing 18% and losing 6%. Analysis_of_the difference in efficiency_in the use of_water needs_in each Irrigation Area is an increase_ of 10.5%, an increase of 24.33%, an increase of 40.55% and decrease of 34.8%.